2017
DOI: 10.1089/cmb.2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

A Linear-Time Algorithm for the Copy Number Transformation Problem

Abstract: Problems of genome rearrangement are central in both evolution and cancer. Most evolutionary scenarios have been studied under the assumption that the genome contains a single copy of each gene. In contrast, tumor genomes undergo deletions and duplications, and thus, the number of copies of genes varies. The number of copies of each segment along a chromosome is called its copy number profile (CNP). Understanding CNP changes can assist in predicting disease progression and treatment. To date, questions related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…position (we note that in [24], null positions make the problem more complex, but not here). In particular, the hardness also holds if only deletions are allowed.…”
Section: Strong Np-hardnessmentioning
confidence: 93%
See 2 more Smart Citations
“…position (we note that in [24], null positions make the problem more complex, but not here). In particular, the hardness also holds if only deletions are allowed.…”
Section: Strong Np-hardnessmentioning
confidence: 93%
“…We consider amplification and deletion events, which respectively have the effect of increasing and decreasing the number of copies in a chromosome. As in [22,24], we assume that events affect a set of positions that are contiguous in the reference chromosome.…”
Section: Preliminary Notionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose a greedy algorithm ( Table S1 ) which guarantees to find an optimal solution within a runtime of O ( m ) ( Appendix ), where m is the size of the array 55 . We add an additional restriction that MED equals to infinity, if the copy number at any site is going from 0 to any other number.…”
Section: Methodsmentioning
confidence: 99%
“…MEDICC ( Schwarz et al , 2014 ), the first algorithm to compute the CND, uses a heuristic to reconstruct a phylogenetic tree from CNPs, and has been used successfully in several cancer studies ( Mangiola et al , 2016 ; Schwarz et al , 2015 ; Sottoriva et al , 2015 ). More recently, Zeira et al (2017) showed that the CND between a pair of profiles can be computed in linear time and El-Kebir et al (2017) gave an integer linear programming formulation for reconstructing a phylogenetic tree between CNPs with the minimum number of events.…”
Section: Introductionmentioning
confidence: 99%